Evaluation of two nucleophilic syntheses routes for the automated synthesis of 6-[18-F]fluoro-l-DOPA - Pretze, Marc; Wängler, Carmen; Wängler, Björn (Nuclear medicine and biology, 2017)
Two different strategies for the nucleophilic radiosynthesis of [18F]F-DOPA were evaluated regarding their applicability for an automated routine production on an Ecker&Ziegler Modular-Lab Standard module. Initially, we evaluated a promising 5-step synthesis based on a chiral, cinchonidine-derived phase-transfer catalyst (cPTC) being described to give the product in high radiochemical yields (RCY), high specific activities (AS) and high enantiomeric excesses (ee). However, the radiosynthesis of [18F]F-DOPA based on this strategy showed to be highly complex, giving the intermediate products as well as the final product in insufficient yields for automatization. Furthermore, the automatization proved to be problematic due to incomplete radiochemical conversions and the formation of precipitates during the enantioselective reaction step. Furthermore, the required use of HI at 180°C during the last reaction step led to partial decomposition of lines and seals of the module which further counteracts an automatization. Further on, we evaluated a 3-step synthesis using the commercially available, enantiomerically pure precursor AB1336 for automatization. This synthesis approach gave much better results and [18F]F-DOPA could be produced fully automated within 114min in RCYs of 20±1%, ee of >96%, a radiochemical purity (RCP) of >98% and specific activities of up to 2.2GBq/μmol.
Available online 27 October 2016
Im Titel ist "18" hochgestellt
Gesehen am 24.09.2018